The Influence of Media Coverage and Institutional Investors’ Shareholding Ratio on the Choice of Earnings Management Approaches - QIAO, LU (2018)
Abstract In modern corporate governance, external supervisors play an increasingly important role. This paper studies the choice of earnings management methods for UK listed companies in the London Stock Exchange from the perspective of media coverage and institutional investors. It uses a combination of theoretical analysis and empirical analysis, and through the robustness tests, the following reliable conclusions are obtained. First, under the influence of media coverage, managers are more inclined to choose real earnings management. In addition, under the influence of institutional investors, managers are more likely to choose real earnings management. Moreover, this paper evaluates the simultaneous impact of media coverage and institutional investors on the choice of earnings management methods. The results show that media coverage has effect on the relationship between institutional investor and earnings management. However, institutional investors do not affect the relationship between media coverage and earnings management. Finally, the paper describes the shortcomings of this research. In addition, it proposes some suggestions for strengthening the supervision of external supervisors on earnings management behaviours. Moreover, recommendations are made to inform future study about the impact of external supervisors on earnings management.